Implementasi Kurikulum Merdeka dalam Pembentukan Karakter SD Negeri Kepadangan 2 - Yulianti Tri Pratiwi; Nanda Veruna Enun Kharisma (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character education can instill character values ​​in students as a foundation for forming a quality generation that is able to live independently in everyday life. The problems at SD Negeri Kedangan 2 do not only cover classroom learning activities, but also extracurricular activities that play an important role in character development and support school culture. The purpose of this study is to describe the implementation of the Independent Curriculum at SD Negeri Kedangan 2. The BKP independent internship activity will be carried out individually and will start on September 2, 2024 to November 29, 2024. The independent internship activity at SD Negeri Kedangan 2 begins with an initial orientation where interns get to know the school environment, learn the organizational structure, and get information about: Study programs are introduced. The implementation of the MBKM Mandiri internship program at SDN Kedangan 2 provides a very valuable experience for both students and schools. The educational and extracurricular activities carried out make a positive contribution to the development of students' academic and personal skills. Innovative programs such as literacy visits, greening, and anti-bullying programs create a friendlier learning environment and support the goals of the Independent Curriculum.